The Chinese : Photography and video from China. - Lütgens, Annelie; Smith, Karen; van Tuyl, Gijs; Exhibition. The Chinese : Photography and video from China. Kunstmuseum Wolfsburg. 2004-10-09. 2005-01-09 (Wolfsburg : Kunstmuseum Wolfsburg, 2004)
Hai Bo ; Hong Hao ; Hou Bo ; Xu Xiaobing ; Liu Zheng ; Ou Ning ; Cao Fei ; Siao, Eva ; Song Yongping ; Wang Jinsong ; Wang Qingsong ; Weng Fen ; Xiang Liqing ; Xing Danwen ; Yang Fudong ; Yang Yong ; Yang Zhenzhong ; Zheng Dasheng ; Zhou Hongxiang ; Zhou, Xiaohu ; Zhuang Hui
bibliog. p. 142-143
biog. p. 129-141
Engels
boek
Keywords: China